INTERAKSI SPASIAL DALAM PEMANFAATAN RUANG DARATAN DAN PESISIR DI KAWASAN MANDEH PESISIR SELATAN - Sartika, Dewi (DEPARTEMEN GEOGRAFI FIS UNP, 2025)
Interactions that occur socially, economically and ecologically in land and coastal areas often cause problems, such as ecosystem damage that causes a decrease in ecological quality. In addition, changes that occur in coastal areas are very dynamic along with an increase in population and an increase in the need for land for economic activity. This study aims to identify zoning of space allocation in accordance with its designation in Koto XI Tarusan District. The research method used in this study is the Marxan analysis method with the Zonae Cogito tool. The results of this study show that conservation areas for mangrove and coral reef areas are classified into 5 classes, with solution areas that have high frequencies or highly recommended areas that have an area of 702 Ha and conservation areas with low or highly unrecommended frequencies have an area of 2432 Ha. So the area identified as zoning the appropriate allocation for conservation is 702 Ha. Keywords: Marxan, Zonae Cogito, Conservation